Coagulation Treatment of Wastewater: Kinetics and Natural Coagulant Evaluation - Nomthandazo Precious Sibiya; Sudesh Rathilal; Emmanuel Kweinor Tetteh (Molecules, 2021)
In this study, three coagulants (ferromagnetite (F), alum (A), and eggshells (E)) and their hybrids (FA, FE, and FEA) were investigated as possible cost-effective coagulants for the treatment of industrial wastewater. Scanning electron microscopy (SEM) coupled with energy-dispersive X-ray (EDX) was used to characterize the morphological and elemental compositions of the coagulants. The effects of coagulant dosage (10–60 mg/L) and settling time were investigated for the removal of turbidity, color, and total suspended solids. A jar tester (JTL6) operating at conditions of 150 rpm for 2 min (rapid mixing) and 30 rpm for 15 min (slow mixing) was employed. Results from the characterized supernatant showed about 80% removal of the contaminants. The prospects of F were proven to be the most effective as compared to the binary (FA > FE) and the ternary hybridized (FEA) coagulants. At an optimum dosage and settling time of 20 mg/L and 30 min, respectively, the treatability performance of F was clearly proven to be viable for wastewater treatment.